The (mis)match between civil society organisations and individual citizen participation - Berkvens Liese; Bram Verschuere (International Review of Public Policy)
Governments increasingly engage individual citizens in the policy-making process and also in contexts where civil society organisations (CSOs) traditionally play a substantial role in this process by advocating for the interests and needs of their constituencies. Moreover, CSOs are in the position to enhance or obstruct different modes of individual citizen participation. The question of under which circumstances do CSOs find citizen participation modes legitimate is therefore important. We performed a multiple case study fitting a theoretical framework consisting of four different modes of individual citizen participation in local governments that affect CSOs. Our analyses are based on a framework of perceived legitimacy, including input, throughput and output legitimacy. Our results show that CSOs’ perceptions of legitimacy vary depending on the individual citizen participation mode and are nuanced by CSOs’ role in the initiative and by their trust in the local government.